Kuntai capsule attenuates premature ovarian failure through the PI3K/AKT/mTOR pathway. (15th July 2019) - Zhang, Han; Qin, Fenfen; Liu, Anlong; Sun, Qinmei; Wang, Qisheng; Li, Qian; Lu, Shengfeng; Zhang, Dong; Lu, Zhigang
Abstract: Ethnopharmacological relevance: Kuntai capsule (KTC), a type of herb formulas, was first described in the book of Shang Han Za Bing Lun in the third century. KTC has been widely used for the clinical treatment of menopausal syndrome. Considering that premature ovarian failure is also known as premature menopause, this study was designed to investigate the effects and mechanisms of KTC on a mouse model of premature ovarian failure. Materials and methods: Forty-five female C57BL/6 mice were chosen for this study. Fifteen of the mice were separated into the Control group. The remaining thirty were used to establish the premature ovarian failure model by injecting intraperitoneally with 75 mg/kg cyclophosphamide and then by randomly dividing the mice into two groups. One group was considered the Model group, the other group treated with the Kuntai capsule intragastrically every day for one week called the KTC group. After treatment, mice were sacrificed for sampling. The ovaries morphology of mice was observed by hematoxylin and eosin (HE) staining, and all follicles were counted under microscope. Western blotting was used to detect the PI3K/AKT/mTOR pathway activation. Serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2 ) and anti-mullerian hormone (AMH)levels were measured by enzyme-linked immunosorbent assay (ELISA). The fertility was observed by giving treated mice 8 weeks for breeding. Results: We found that primordial follicle counts were increased in the KTC group compared to the Model group. The phosphorylation of PI3K, AKT, mTOR, 4E-BP1 and S6K in the KTC group significantly reduced compared to Model group. Serum FSH and LH levels in the KTC group were decreased compared to the Model group, while, serum E2 and AMH levels in the KTC group were increased compared with the Model group. The litter size in the KTC group was improved compared to Model group. Conclusions: The KTC showed protective potentials of ovarian reserve and fertility to attenuate premature ovarian failure, which was relatively associated with activation of the PI3K/AKT/mTOR signaling pathway. Graphical abstract: Image 1